The Monk versus the Philosopher: From the History of the Bulgarian-Byzantine War 894-896 - Leszka, Mirosław J. (Studia Ceranea, 2011)
The article is devoted to a few problems: 1 how Symeon and Leo the Philosopher looked at the Bulgarian-Byzantine war of 894–896; 2. what place it took in their life experiences; 3 how it was inscribed in the concept of relations between countries whose inhabitants follow the same religion. The war of the years 894–896 showed that Symeon was not only a cabinet scholar and a former monk, but a statesman, a gifted leader, skillful and ruthless negotiator. This war made him realize his own strength and gave him an opportunity to test his skills as a leader and a ruler. The war also demonstrated to the Byzantines that the Bulgarians, although they were Christians, were still dangerous opponents. Leo VI, a wise man and a scholar suffered a great defeat in dealing with just as scholarly but much more determined and gifted with military talents Bulgarian ruler. The former Monk defeated the Philosopher.